Thymidine phosphorylase expression in Kaposi sarcoma. Issue 5 (May 1996) - Dada, M A; Boshoff, C H; Comley, M A; Turley, H; Schneider, J W; Chetty, R; Gatter, K C
Abstract : AIMS: To examine the immunohistochemical distribution of thymidine phosphorylase (TP) in all clinicopathological subtypes of Kaposi sarcoma. METHODS: Thirty two biopsy specimens of Kaposi sarcoma (29 patients) were studied. Six of these patients represented classic, six endemic, eight HIV associated, seven post-immunosuppression/transplant related, and two unclassified variants of Kaposi sarcoma. The average age was 49 years (range 22-83 years) and the male: female ratio 24:5. Four samples of angiosarcoma and one of spindle cell haemangio-endothelioma were stained in parallel. All specimens were fixed in formalin, embedded in paraffin wax and processed routinely. Immunohistochemistry was carried out using an antibody directed against CD31 (JC70) and the monoclonal antibody P-GF.44C against TP. RESULTS: All biopsy specimens showed immunoexpression for TP. The spindle cell component stained more strongly than newly formed endothelium lined vessels and normal, resident vessels at a distance from the lesions. CONCLUSIONS: The strong immunoexpression of TP suggests up-regulation of TP and a role for TP in angiogensis in Kaposi sarcoma. The mechanism for the up-regulation of TP remains unknown, but viral infections may trigger it. The differential staining of the various cell components of Kaposi sarcoma also suggest that TP either plays a role in the differentiation and maturation of Kaposi sarcoma or is a reflection of such changes.